2024
DOI: 10.1155/2024/5570011
|View full text |Cite
|
Sign up to set email alerts
|

Oil Palm Biomass Sap-Rotten Rice as a Source to Remove Metal Ions and Generate Electricity as By-Products through Microbial Fuel Cell Technology

Anoud Saud Alshammari,
Ghada Mohamed Aleid,
Alamri Rahmah Dhahawi Ahmad
et al.

Abstract: Microbial fuel cell (MFC) is a new and interesting technology that can be used to treat wastewater without using electricity. The current research focuses on electron generation, which is one of the technique’s major challenges. According to the latest literature, the study was planned to successfully remove the metals from artificial wastewater at high concentrations and generate electricity. On average, after 18 days of operation, it offered 610 mV with 1000 ῼ constant external resistance. The internal resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The high voltage values observed are due to the biofilm area formed by the adhesion between the community of microbes present that was diverse and active [33]. On the contrary, the decrease in the electrical potential values is due to the end of the organic oxidation processes, while the decrease in the last days is due to the microbial reduction rate [34]. Furthermore, the literature has reported that the increases in electrical potential are due to the inoculation of fresh waste; organic matter wears out, causing a decrease in potential values [35].…”
Section: Results and Analysismentioning
confidence: 94%
“…The high voltage values observed are due to the biofilm area formed by the adhesion between the community of microbes present that was diverse and active [33]. On the contrary, the decrease in the electrical potential values is due to the end of the organic oxidation processes, while the decrease in the last days is due to the microbial reduction rate [34]. Furthermore, the literature has reported that the increases in electrical potential are due to the inoculation of fresh waste; organic matter wears out, causing a decrease in potential values [35].…”
Section: Results and Analysismentioning
confidence: 94%
“…The degradation of metal ions toxic to living beings using sugar-based substrates is one of the novel techniques in this field; for example, Omenesa et al (2023) managed to reduce the concentration of Pb 2+ by 89% using single-chamber microbial fuel cells with graphite electrodes in 12 days, where they used wastewater as a substrate, to which 50 g of sugar was added in 500 mL of substrate; they managed to generate peaks of 150 mV with a power density of 0.108 mW/m 2 [66]. Alshammari et al (2024) in their research managed to generate peaks of 610 mV with a power density of 3.164 mW/m 2 and managed to reduce different types of heavy metals, with Ni 2+ being the one that decreased the most (95.99%); they also mentioned that the MFC technology will be easily adapted because its The reduction of various heavy metals has been investigated using microbial fuel cells of different designs and electrodes of different materials; some of the most recent ones can be seen in Table 4. One of the most important aspects is the reduction in costs to solve two environmental problems (eliminating heavy metals in water and generating bioelectricity).…”
Section: Results and Analysismentioning
confidence: 99%
“…A. (2024) studied an MFC with synthetic wastewater, managing to reduce Cu (II), Mg (II), Mn (II), Zn (II), and Na by 93 85, 93, 88, and 36%, respectively, and mentioned that bacterial nanowires are also formed in toxic environments and are responsible for the elimination of toxic ions present in the substrate and, at the same time, allow a higher rate of electron transport, generating greater efficiency in the MFC [68]. Other metal ions (lead, cadmium, chromium, and copper) have also been reduced using MFCs, highlighting the importance of the physiological activity of biofilms and extracellular polymeric substances for the reduction of these metals, where the use of nanoparticles and anodic and cathodic biosynthesis are the most notable points [69,70].…”
Section: Results and Analysismentioning
confidence: 99%